Potential Application of Short Encapsulation Pull Test (Sept) Data to Project Relative Roof Control Risk - Jason E. Tinsley; Yoginder Paul Chugh (International Conference on Ground Control in Mining, 2016)
"Over the last five years, the authors have compiled a database of Short Encapsulation Pull Test (SEPT) evaluations from Interior Basin (Basin) coal mines. Typically, SEPT data are analyzed to obtain peak load carrying capacity per unit length of resin encapsulation designated as the ""Grip Factor,"" or GF. In a previous paper, ""An Analysis of Short Encapsulation Bolt Pull Test (SEPT) Data From Interior Basin Coal Mines,"" authors analyzed tangent value of the load-displacement curve as Anchorage Stiffness at 50% (AS-50) of the peak load, or GF value, to assess reinforcement potential of an installed bolt system. This paper attempts to correlate the secant AS VALUES (of SEPT on 6 ft (1.8 m) long installed bolts at a lower load of about four tons from several different mines in the Basin with their MSHA-approved primary support requirements. Since the current regulatory environment requires plan changes dynamically to ensure that roof falls are minimized, the authors hypothesize that the practiced roof control plan must meet the minimum requirement of adequately supporting immediate roof strata. The analyses are based on 181 SEPT studies performed by Minova professionals. Analyses indicate a macrolevel correlation for both roof support density and roof support cost that may have the potential to be used by mine operators to compare their performance with other mines in the area. Limitations of the analyses include ignoring mining depth, mining height and required secondary supports as part of the requirements for a roof control plan. The authors recommend additional analyses to develop this concept further to develop guidelines that can be confidently used by coal companies.INTRODUCTIONPartially- and fully-grouted bolts are extensively used in coal mines for roof support as part of MSHA-approved roof control plans. Since grouted bolts have a larger area of contact with the rock, they can develop much greater anchorage capacity than conventional expansion shell (point-anchored) bolts. Load transfer characteristics and interaction mechanics between steel rebar, grout and rock mass around the bolt hole for grouted bolts are generally assessed in the laboratory or field though short-encapsulation pull tests (SEPT), which have been extensively researched by Aziz and Jalalifar (2005), Aziz (2004a), Serbousek and Signer (1987), Signer (1990), and Mark et al. (2002), among others. In a SEPT, about 12 in. (30 cm) of bolt length is typically encapsulated in resin and a pull test is performed to collect load-displacement data prior to failure and, in some cases, post-failure. A typical load-displacement data set for a bolt is shown in Figure 1. SEPT characteristics are designated by peak load carrying capacity, or grip factor, which is the peak load carrying capacity per unit length of resin encapsulation. SEPT is routinely used to assess anchorage performance characteristics of different lithologies overlying a coal seam to identify type of bolt, bolt diameter, length and spacing across and along an excavation. Anchorage stiffness, or AS, at any load may also be calculated as the tangent or secant value of the slope of the load displacement curve at a particular load level. Anchorage Stiffness characteristics of bolts from SEPT data have typically not been considered in any depth until recently (Chugh et al., 2014; Chugh et al., 2015)."